Kesehatan Mental Siswa Pasca Pembelajaran Daring di SMA N 2 Pulau Punjung Kabupaten Dharmasraya - Rahmadani, Desi; Putra, Dodi Pasila; Afrinaldi, Afrinaldi; Syawaluddin, Syawaluddin (Darul Yasin Al Sys, 2024)
This study was motivated by the fact that some students felt stressed, had feelings of insecurity and discomfort with the changing learning system. They also often feel tired, lethargic in the teaching and learning process, they also often experience anxiety and feelings of stress. Some students also feel less confident, less good at understanding themselves, and less satisfied with their social relationships so that they do not feel happy with the learning system and they also find it difficult to adapt to their environment as a result of post-online learning. This type of research is descriptive qualitative research that describes the mental health of students after online learning at SMAN 2 Pulau Punjung. In collecting data, researchers used observation and interview techniques. Meanwhile, to analyze it, researchers used data reduction, data presentation, and data verification steps. The results of the study showed that the mental health of students after carrying out online learning at SMAN 2 Pulau Punjung, namely students have good mental health. More students have good mental health than bad, students have a healthy mentality characterized by students feeling comfortable and safe while studying, having high self-confidence, being able to understand themselves, getting satisfaction in social relationships (social interactions), having emotional maturity that is appropriate for their age, not having a disturbed personality, and being able to adapt to their environment and being happy with their current situation.